Role of miR-506 in ulcerative colitis associated with primary sclerosing cholangitis - Agnieszka Kempinska-Podhorodecka; Monika Adamowicz; Ewa Ostrycharz; Mateusz Chmielarz; Maciej Wójcicki; Piotr Milkiewicz; Malgorzata Milkiewicz (Scientific Reports, 2021)
Abstract Primary sclerosing cholangitis (PSC) is commonly accompanied by ulcerative colitis (UC). MicroRNA-506 modulates expression of genes which are essential for sphingosine-mediated signaling pathway and intestinal mucosa protection. We investigated whether miR-506 and its target genes are involved in phenotypic presentations of colonic inflammation and/or neoplasia. We analyzed serum and colon tissue samples collected from patients with PSC, PSC with concurrent UC (PSC + UC), UC alone, and healthy controls (n = 10 each). MiR-506 was substantially upregulated in ascending colons of PSC and PSC + UC patients, in contrast to sigmoid colons of PSC and UC patients. Upregulation of miR-506 was associated with inhibition of SPHK1, AE2, InsP3R3, and p53. Colonic suppression of miR-506 presented in UC was accompanied by substantially increased DNMT1, SPHK1, and S1P lyase expressions. A functional in vitro analysis in Caco-2 cells showed that the induction of miR-506 activity by miR-506 mimic or GDCDA bile acid suppressed, whereas inhibition of miR-506 by miR-506 inhibitor or lipopolysaccharide (LPS) upregulated the expression of the examined target genes. A different phenotypic presentation of colitis may be related to miR-506 expression. In ascending colons with PSC + UC, upregulation of miR-506 may result in failure of bicarbonate secretion and inhibition of p53, which predisposes to pro-tumorigenic transformation. In contrast, downregulation of miR-506 enhances S1P production, leading to pro-inflammatory signaling.